“Requerimiento nutricional del clutivo de ajonjolí (sesamun orientale L.) bajo condiciones agroclimaticas de la localidad de la banda de shilcayo- E. E. Juan Bernito” - Estrella Tenazoa, Saúl (2015)
The research was conducted in 2013 at the lnstítute of Tropical Crops (ICT), Experimental Station Juan Bernito district of Shilcayo geographically located at 06 º 30 '07" south latitude and 76 º 20' 09 " west longitude with an altitude of 360 msnmm. The work consisted of evaluating the "nutritional requirement of the crop of sesame (Sesamum orienta/e L.) under agro-climatic conditions of the locality Shilcayo Bernito Juan-ee" applied according to soil test NPK in an area of 191 m2 with 7.5 cm spacing between plants, 30 cm between groove street between treatments 1 m and 2m Street between machining blocks in soil; the application of fertilizers will be made at time of planting and at two months after planting. The treatments were TO (control), T1 (10/25/25), T2 (50-20-50), T3 (75-30-75), assessments were performed every 7 days. Design was completely randomized with tour treatments and three blocks. Variables evaluated and analyzed statistically were: plant height, stem diameter, % chlorophyll, days to flowering, fruiting and crop, number of branches, fruit weight, seed weight, yield, plant tissue analysis, oíl volume. Statistical analysis showed that this treatment T3 gets better result in height, stem diameter, % chlorophyll, fruit weight, number of branches, oil volume and improves plant phenological stage.